Increasing the growth and yield of shallot (Allium cepa L. Aggregatum group) by using Methyl Jasmonic Acid (MeJA) concentrations under drought condition - Rizqi Dyah Susilowati; Endang Sulistyaningsih; Rudi Hari Murti (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
Drought is one of the limiting factors for plant production, and there is a continuous demand for drought tolerant plants. Shallots are considered a shallow-rooted crop and have been reported to have little tolerance to drought conditions. One of the efforts to increase plant tolerance to drought conditions is through the addition of Methyl Jasmonic Acid (MeJA). MeJA is involved in several physiological and biochemical procedures in plant growth and development. Application of MeJA can increase the plant tolerance to drought conditions through chlorophyll synthesis, stomatal conductivity, transpiration, net photosynthetic rate and biomass production. This research was conducted in a complete randomized block design with three replications to determine the response of shallot plants to the application of MeJA (0 µM, 25 µM, 50 µM and 100 µM) under drought conditions, which was simulated through the frequency of watering (once daily, every other day, once in three days). Soil water content calculated before the watering treatment was 24.45%, 20.34% and 18.45% for watering once daily, every other day, once in three days, respectively. The results showed that the addition of MeJA played a role in enhancing the growth and productivity of shallot plants under normal and drought conditions. Application of 50 µM of MeJA could increase the Water Use Efficiency, maintain the Relative Water Content, increase the width of stomatal aperture, and increase the leaf area and Leaf Area Index. This also led to increasing Net Assimilation Rate and Plant Growth Rate. Application of 50 µM of MeJA gave in increasing bulb productivity and reached 7.86 ton.ha-1, which was 58.2 % higher than that of in control (without MeJA application). Application of MeJA to shallot plants exhibited avoiding type of physiological tolerance.